Regulation of systemic autoimmunity and CD11c(+) Tbet(+) B cells by SWEF proteins - Manni, Michela (Cell Immunol, 2017)
Recent studies have revealed the existence of a T-bet dependent subset of B cells, which expresses unique phenotypic and functional characteristics including high levels of CD11c and CD11b. In the murine system this B cell subset has been termed Age/autoimmune-associated B cells (ABCs) since it expands with age in non-autoimmune mice and it prematurely accumulates in autoimmune-prone strains. The molecular mechanisms that promote the expansion and function of ABCs are largely unknown. This review will focus on the SWEF proteins, a small family of Rho GEFs comprised of SWAP-70 and its homolog DEF6, a newly identified risk variant for human SLE. We will first provide an overview of the SWEF proteins and then discuss the complex array of biological processes that they control and the autoimmune phenotypes that spontaneously develop in their absence, highlighting the emerging involvement of these proteins in regulating ABCs. A better understanding of the pathways controlled by the SWEF proteins could help provide new insights into the mechanisms responsible for the expansion of ABCs in autoimmunity and potentially guide the design of novel therapeutic approaches.